Fairness and the unselfish demand for redistribution by taxpayers and welfare recipients - Fabio Sabatini; Marco Ventura; Eiji Yamamura; Luca Zamparelli (Economics and Econometrics Research Institute (EERI), 2017)
We illustrate how the desire to live in a fair society that rewards individual effort and hard work triggers an unselfish though rational demand for redistribution. This leads the well off to prefer higher taxes and the poor to reject extreme progressivity. We then provide evidence of these behaviors using a nationally representative survey from Italy. Our empirical analysis confirms that a stronger aversion to unfair distributive outcomes is associated with a higher support for redistribution by individuals with high income and to a lower demand for redistribution by those with low income.
Keywords: H10; H53; D63; D69; Z1; 330; Fairness; income distribution; inequalities; taxation; welfare; redistribution; free-riding; civic capital; social capital